A novel multi-parametric deformability and impedance cytometer for single cell biophysical studies - Yang, Haoning (Nanyang Technological University, 2021)
Single cell biophysical properties provide important information related to cell status and phenotype, which can be exploited for immune health profiling, clinical diagnosis, and monitoring of treatment interventions. While measurement methods for biophysical properties such as electrical impedance and size are well established, measuring cell deformability remains complicated and costly as expensive microscopes and high-speed cameras are required for high resolution cell imaging. This project aims to develop a novel label-free microfluidic device that can measure multiple cellular biophysical properties including cell size and deformability using impedance cytometry. Viscoelastic cell focusing was used in the device to focus cells to a single position to facilitate optical and electrical measurements, while cell deformation was induced by hydrodynamic stretching in a cross junction. We first characterized the device using HL60 (leukemia cell line) of different phenotypes (untreated, paraformaldehyde (PFA)-fixed, differentiated HL-60). PFA-treated HL60 exhibited lower electrical deformability as compared to control whereas differentiated HL60 had higher electrical deformability with smaller cell size. The comparative studies of cell deformability index between optical measurement and electrical measurement also showed a good linear correlation (R2=0.9370). As a proof-of-concept for clinical testing, we tested primary neutrophils isolated from healthy and type 2 diabetes mellitus (T2DM) donors. In native state, there were negligible differences in cell size and deformability between healthy and diabetic neutrophils. Interestingly, upon treated with agonist N-Formylmethionyl-leucyl-phenylalanine (fMLP), significant deformability changes were observed for diabetic neutrophils which indicates the feasibility to characterize biophysical-functional changes of immune cells in T2DM patients. Overall, this platform provides a fast and low-cost solution for multi-parametric single cell biophysical characterization which can be further integrated with other modalities towards clinical applications.